If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+3x-9x-2=0
We add all the numbers together, and all the variables
-1x-2=0
We move all terms containing x to the left, all other terms to the right
-x=2
x=2/-1
x=-2
| -1=3-2x | | 10p=-6 | | 9=r=2 | | (6x)-(2/9x^-(4/3))=0 | | 3(x-2)-5(2x+1=2 | | 9+7x+4x=86 | | 2 = 8j | | 8r+9=168 | | 5^(1-9x)=6^x | | 5x-10=6x+72 | | 16w^2-3w+1=0 | | 8r+ 9= 168 | | 2^2-2x-340=0 | | 8 r+ 9= 168 | | 1.286=2^x | | 5^(x^2)=50 | | x+6x-8=4x | | 5x-10=3(2x+12) | | 2q=74 | | x+10+6x=52 | | -3=y-6 | | b=63/9 | | j=54+10 | | 1.9v-4.002=3v-2.48v | | 5x+3x=32-2x | | 15+14(6x)=95 | | 48/8=g | | 36=30+2x | | w=32/4 | | 3/8+p/8=27/8 | | x+2x+2x+2=60 | | -1=3-2x=10 |